Population dynamics of mosquitoes (Diptera: Culicidae) and their disease-harboring rates in Gyeonggi province, South Korea - Jung, Minhyung; Kim, Soowan; Lee, Doo-Hyung (Journal of Asia-Pacific entomology, 2021)
[Display omitted] •Population dynamics of mosquitoes were monitored from 2017 to 2019 in South Korea.•Population peak was observed in August and September from survey sites conducted.•Dominant mosquito species were varied between suburban residential and rural area.•From the pools tested, three pools were positive for Japanese encephalitis virus. Population dynamics and species composition of mosquitoes were monitored in a suburban residential area and rural areas, including a migratory bird refuge area and a cattle farm area, from 2017 to 2019. Mosquitoes were collected every two weeks using one BG sentinel trap and two black-light traps in a suburban residential area and a migratory bird refuge area, and one black-light trap in a cattle farm area from March to November. From the surveillance, a total of 13,267, 9,697 and 6,688 mosquitoes were collected in 2017, 2018, and 2019, respectively. The peak of the mosquito population was observed in August and September in both the suburban residential area and rural areas. In general, Culex pipiens pallens was the dominant species in the suburban residential area, whereas Aedes vexans nipponii and Anopheles spp. were the most dominant in the rural areas. Collected mosquitoes were pooled into groups for each collection site and species to investigate flavivirus harboring. Three pools were positive for Japanese encephalitis virus type V, one pool was positive for Chaoyang virus, and six pools were positive for Culex flavi virus from the 731 pools tested. When total numbers of collected mosquitoes were further analyzed by linear regression analysis for their interaction with ambient temperature and relative humidity, the number of mosquitoes were significantly affected by the ambient temperature. In contrast, relative humidity was significantly affecting the total number of mosquitoes only for the migratory bird refuge area.